LITERATURE REVIEW: PENILAIAN DIRI DAN PENGAPLIKASIAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) DI MADRASAH IBTIDAIYAH - M Choirul Muzaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This literature review study is motivated by the challenges of world development, especially in the development of learning interpretations that are increasingly demanding the availability of human resources (HR) who master science and technology (IPTEK). Technological and Content Knowledge can be an alternative to be used as a reference for educators in the context of developing learning with a new, better model. This study aims to gather information from several articles related to self-assessment and to apply technological pedagogical and content knowledge in learning natural and social sciences (IPAS) in elementary schools. The results of this literature review can be used as reference material in the development of learning tools in the current 4.0 era. Various studies related to technology pedagogical content knowledge (TPACK) and pedagogical content knowledge (PCK), both of which are important for developing the professional skills of a teacher and prospective teachers. Based on the literature review, it was found that among the needs in the development of learning tools lies in the ability of an educator to master the TPACK (Technological Pedagogical and Content Knowledge) concept.